Prevalence, antimicrobial resistance, and staphylococcal toxin genes of blaTEM‐1a‐producing Staphylococcus aureus isolated from animals in Chongqing, China. Issue 1 (10th December 2022) - Dong, Qingshuang; Wang, Qing; Zhang, Yun; Chen, Yao; Wang, Haoju; Ding, Honglei
Abstract: Background: Staphylococcus aureus infection of livestock animals and humans is a major public health issue. There are reports of antimicrobial resistance and multiple staphylococcal superantigen genes in many countries and several provinces of China, but the status in Chongqing, China is uncertain. Objectives: The aim of this study was to determine the prevalence, antimicrobial susceptibility, and other molecular characteristics of S. aureus isolates from livestock animals in Chongqing. Methods: Staphylococcus aureus was isolated and identified by selective enrichment and amplification of the nuc gene from 1371 samples collected at farms in Chongqing. The agar dilution method was used to determine the resistant phenotype, and extended spectrum β‐lactamase genes were amplified by PCR. Methicillin‐resistant S. aureus was verified by the presence of the mecA gene, and the presence or absence of SE, SEl, and TSST‐1 genes was detected in the isolates. Results: We cultured 89 S. aureus isolates from 1371 samples between March 2014 and December 2017. These isolates were from pigs, cattle, goats, rabbits, and chickens. There were four methicillin‐resistant S. aureus strains (three from pigs and one from a chicken). The 89 isolates had high resistance to penicillin (93.3%) and ampicillin (92.1%), but most were susceptible to amikacin and ofloxacin, with resistance rates below 10%. A total of 62.9% of the isolates had varying degrees of multidrug resistance. Almost all strains, except for three isolates from chickens, were positive for bla TEM‐1a . There were 19 of 20 tested staphylococcal SE/SEl/TSST‐1 genes present (all except for seq ), and the predominant genes were sei (58.4%), tst‐1 (56.2%), and seg (51.7%). Conclusions: The high antimicrobial resistance and prevalence of bla TEM‐1a reinforce the need to reduce the usage of antimicrobials in livestock. The universal existence of staphylococcal toxin genes implies a potential threat to public health by animal‐to‐human transmission via the food chain. Abstract : The average isolation rate of livestock‐associated S. aureus is 6.5%, and the S. aureus isolates showed high resistance to a wide range of antimicrobials. Most strains, with the exception of three chicken‐associated strains, harbored bla TEM‐1a gene. All S. aureus isolates, except one rabbit‐associated strain, carried one or more staphylococcal toxin genes.